Dietary intake and blood concentrations of antioxidants and the risk of cardiovascular disease, total cancer, and all-cause mortality: a systematic review and dose-response meta-analysis of prospective studies - Aune,D; Keum,N; Giovannucci,E; Fadnes,LT; Boffetta,P; Greenwood,DC; Tonstad,S; Vatten,LJ; Riboli,E; Norat,T (American Journal of Clinical Nutrition, 2018)
Background: High dietary intake or blood concentrations (as biomarkers of dietary intake) of vitamin C, carotenoids, and vitamin E have been associated with reduced risk of cardiovascular disease, cancer, and mortality, but these associations have not been systematically assessed. Objective: We conducted a systematic review and meta-analysis of prospective studies of dietary intake and blood concentrations of vitamin C, carotenoids, and vitamin E in relation to these outcomes. Design: We searched PubMed and Embase up to 14 February 2018. Summary RRs and 95% CIs were calculated with the use of random-effects models. Results: Sixty-nine prospective studies (99 publications) were included. The summary RR per 100-mg/d increment of dietary vitamin C intake was 0.88 (95% CI: 0.79, 0.98, I2 = 65%, n = 11) for coronary heart disease, 0.92 (95% CI: 0.87, 0.98, I2 = 68%, n = 12) for stroke, 0.89 (95% CI: 0.85, 0.94, I2 = 27%, n = 10) for cardiovascular disease, 0.93 (95% CI: 0.87, 0.99, I2 = 46%, n = 8) for total cancer, and 0.89 (95% CI: 0.85, 0.94, I2 = 80%, n = 14) for all-cause mortality. Corresponding RRs per 50-μmol/L increase in blood concentrations of vitamin C were 0.74 (95% CI: 0.65, 0.83, I2 = 0%, n = 4), 0.70 (95% CI: 0.61, 0.81, I2 = 0%, n = 4), 0.76 (95% CI: 0.65, 0.87, I2 = 56%, n = 6), 0.74 (95% CI: 0.66, 0.82, I2 = 0%, n = 5), and 0.72 (95% CI: 0.66, 0.79, I2 = 0%, n = 8). Dietary intake and/or blood concentrations of carotenoids (total, β-carotene, α-carotene, β-cryptoxanthin, lycopene) and α-tocopherol, but not dietary vitamin E, were similarly inversely associated with coronary heart disease, stroke, cardiovascular disease, cancer, and/or all-cause mortality. Conclusions: Higher dietary intake and/or blood concentrations of vitamin C